Computed tomography scan does not correlate with patient experience of nasal obstruction. (24th November 2015) - Ardeshirpour, Farhad; McCarn, Kate E.; McKinney, Alexander M.; Odland, Rick M.; Yueh, Bevan; Hilger, Peter A.
Abstract : Objectives/Hypothesis: Third‐party payors have begun to demand imaging studies to document septal deviation prior to authorizing septoplasties. This study aims to determine whether septal deviation findings on computed tomography (CT) correlate with symptoms of nasal obstruction as determined by the Nasal Obstruction Symptom Evaluation (NOSE) scale. Study Design: Prospective and retrospective chart review. Methods: Patients 18 years or older undergoing CT scans, which included the nasal septum, were asked to complete a NOSE scale survey and report the laterality of any possible obstruction. Coronal CT images of subjects were graded by two blinded otolaryngologists and two blinded neuroradiologists using a grading system devised by the authors. Results: Seventy‐three subjects met inclusion/exclusion criteria. Interobserver reliability about the degree of septal deviation on CT scans was moderately good to substantial (κ values, 0.43 to 0.72). There was poor correlation between NOSE scores and degree of deviation on CT scans (Kendall's τ, 0.031 to 0.045; P values all >.05). There was poor concordance between the side of symptoms that patients reported and the side that observers thought was most deviated on CT. Conclusions: There is little correlation between septal deviation findings on CT scans and symptoms of nasal obstruction. The results do not support a role for CT scans as either a clinically meaningful or necessary test to investigate uncomplicated nasal obstruction. Level of Evidence: 4 Laryngoscope, 126:820–825, 2016